14 mrad extraction line optics for push-pull - Nosochkov, Y; Moffeit, K; Morse, W; Parker, B; Seryi, A (2007)
The ILC design [1] is based on a single Interaction Region (IR) with 14 mrad crossing angle and two detectors in the "push-pull" configuration, where the detectors can alternately occupy the Interaction Point (IP). Consequently, the IR optics must be compatible with different size detectors designed for different distance L* between the IP and the nearest quadrupole. This paper presents the push-pull optics for the ILC extraction line compatible with L* = 3.5 m to 4.5 m, and the simulation results of extraction beam loss at 500 GeV CM with detector solenoid.